2017
DOI: 10.1007/s11517-017-1745-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D workspace shoulder assessment tool incorporating electromyography and an inertial measurement unit—a preliminary study

Abstract: Traditional shoulder range of movement (ROM) measurement tools suffer from inaccuracy or from long experimental setup times. Recently, it has been demonstrated that relatively low-cost wearable inertial measurement unit (IMU) sensors can overcome many of the limitations of traditional motion tracking systems. The aim of this study is to develop and evaluate a single IMU combined with an electromyography (EMG) sensor to monitor the 3D reachable workspace with simultaneous measurement of deltoid muscle activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Three studies included EMG sensors in their assessment tool in combination with accelerometers [58], IMUs [59] and M-IMU [39]. EMG sensors placed on the biceps, triceps [59] and deltoid muscles [39] provide additional information about upper limb motor function and shoulder assessment, evaluating muscles activity. Quantification of upper limb motion was executed through a wearable device, MYO armband by Thalamic labs, that combines EMG sensors to record electrical impulses of the muscles [7, 87].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included EMG sensors in their assessment tool in combination with accelerometers [58], IMUs [59] and M-IMU [39]. EMG sensors placed on the biceps, triceps [59] and deltoid muscles [39] provide additional information about upper limb motor function and shoulder assessment, evaluating muscles activity. Quantification of upper limb motion was executed through a wearable device, MYO armband by Thalamic labs, that combines EMG sensors to record electrical impulses of the muscles [7, 87].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated a direct relationship between muscle activity amplitude and pain. 25 Aslani et al 26 reported the study of shoulder ROM with a single IMU combined with an EMG sensor to monitor the 3D reachable workspace with simultaneous measurement of deltoid muscle activity, showing that shoulder disorders may be assessed in terms of 3D surface area and with EMG.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the most common measurement tools for clinical evaluation of shoulder performance are mechanical manual systems such as the goniometer, inclinometer and plurimeter. However, mechanical measurement tools have some limitations and provide little information about the quality of movements or the ability to carry out functional tasks [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other valid systems used for human motion analysis include vision-based systems and optoelectronic systems. However, they are relatively expensive and restricted to laboratory settings, and require specific technical expertise [13], [14]. On the other hand, the inertial sensors offer practical alternatives relatively cheaper and portable for kinematic and functional assessment.…”
Section: Introductionmentioning
confidence: 99%